Factors associated with foodborne pathogens and indicator organisms in agricultural soils - Cook, Camryn; Diekman, Clara M.; Weller, Daniel L.; Murphy, Claire M.; Hamilton, Alexis M.; Ponder, Monica; Boyer, Renee R.; Rideout, Steven L.; Maguire, Rory O.; Danyluk, Michelle D.; Strawn, Laura K. (Frontiers in Sustainable Food Systems, 2023)
Soil can be a route for contamination of fresh fruits and vegetables. While growers routinely manage soil nutrient levels, little research exists on the synergistic or antagonistic effects of soil nutrients on foodborne pathogens. Data on foodborne pathogen prevalence in unamended soils is also relatively limited in literature. This study evaluated foodborne pathogen prevalence (Salmonella, Listeria monocytogenes) and concentration of indicator bacteria (total coliforms, generic Escherichia coli) in agricultural soils, and characterized associations between soil properties (e.g., macro- and micro-nutrient levels) and each microbial target. Three Virginia produce farms, representing different regions and soil types, were sampled four times over one year (October 2021-November 2022). For each individual farm visit, composite soil samples were collected from 20 sample sites (25 m2) per farm per visit for microbial and nutrient analysis (n=240). Samples (25g) were processed for Listeria spp. and Salmonella using a modified FDA BAM method; samples (5g) were enumerated for generic E. coli and total coliforms (TC) using Petrifilm. Presumptive Listeria spp. and Salmonella isolates were confirmed by PCR using the sigB and invA genes, respectively. Soil nutrients from each sample were tested and evaluated for their association with each microbial target by Bayesian Mixed Models. Salmonella prevalence was 4.2% (10/240), with 90% (9/10) recovered on Farm C. Listeria spp. and L. monocytogenes prevalence were 10% (24/240) and 2.5% (6/240), respectively. When samples were positive for generic E. coli (107/240), the average concentration was 1.53±0.77 log10 CFU/g. Soil pH was positively associated with L. monocytogenes [Odds Ratio (OR)=5.5] and generic E. coli (OR=4.9) prevalence. There was no association between Salmonella prevalence and any evaluated factor; however, Salmonella was 11.6 times more likely to be detected on Farm C, compared to other farms. Results show pathogen prevalence was relatively low in unamended soils, and that factors influencing prevalence and concentration varied by microbial target and farm.